Wavefront control of laser beam using optically addressed liquid crystal modulator. (18th May 2018) - Huang, Dajie; Fan, Wei; Cheng, He; Xia, Gang; Pei, Lili; Li, Xuechun; Lin, Zunqi
Abstract : An optically addressed liquid crystal modulator for wavefront control of 1053 nm laser beam is reported in this paper. Its working principle, control method and spatial phase modulation capability are mainly introduced. A new method of measuring the relationship between gray level and phase retardation is proposed. The rationality of the curve is further confirmed by designing special experiments. According to the curve, several spatial phase distributions have been realized by this home-made device. The results show that, not only the maximum phase retardation is larger than 2[STIX]x03C0 for 1053 nm wavelength, but also the control accuracy is high. Compared with the liquid crystal on silicon type spatial light modulator, this kind of modulator has the advantages of generating smooth phase distribution and avoiding the black-matrix effect.